COMPARISON OF SETTINGS REGARDING THE DEAD INJECTION APPLICATION IN THE NETHERLANDS AND INDONESIAN COUNTRIES - Paramita Brata, Desak (Ganesha Law Review, 2020)
Countries around the world have different legal systems. But the most commonly known are the Continental European legal system and the Anglo Saxon legal system. Continental European legal system is a legal system based on various legal provisions that have been codified and the example of the State that has this system is the State of Indonesia. Whereas Anglo Saxon is a legal system based on jurisprudence and the example of the State which has this system is the Netherlands. Each country has a different legal system, as well as in medicine. In the medical world known as Euthanasia. Euthanasia is defined as the act of terminating a person's life (or other creatures) on purpose because of the pain that makes him suffer too much. Indonesia has not specifically and firmly set the issue of Euthanasia and this matter is still being debated. The Indonesian Criminal Code does not find any articles that explicitly regulate eutahanasia. However, if observed, there is an article which shows that the prohibition against Euthanasia is article 344 of the Criminal Code, which is a murder carried out with a very and strict request by the victim. It is different from other Continental European countries such as the Netherlands as the first country to legalize Euthanasia. As of 2002, the Netherlands has adopted the concept of Euthanasia into its legal book.